Factors affecting health information resources in central libraries at Iranian universities of medical sciences - Tayebeh Khajeh; Alireza Isfandyari Moghaddam; Behrooz Bayat; Fariborz Doroudi (Tabriz University of Medical Sciences, 2022)
Background: Academic libraries play a crucial and constructive role in managing information resources. Because medical universities have an essential role in promoting public health, the position of libraries at these universities is both important and influential. Therefore, this study investigated factors that affect the provision of health information resources in central libraries at Iranian universities of medical sciences. Methods: This applied-descriptive study reviewed factors affecting the provision of health information resources based on document study and the Delphi method. A total of 62 managers of these central libraries were asked to participate. The sample was based on the fuzzy Delphi technique, which provides a solution in two phases. The data were obtained from a qualitative analysis of interviews and results from a researcher-created questionnaire. Results: Six factors were found to be vital to providing health information resources, including support, maintenance costs, country policies, economics, cooperation with high-tech companies, and political challenges. Some suggestions are given to address the challenges of providing resources; the most important was to create visual and audio media with a high diffusion coefficient. Conclusion: Numerous factors can affect the provision of health information resources at Iranian universities of medical sciences. The foundations of these factors are varied, some stemming from economic fluctuations and others from technological developments.